Statistical and health economic analysis plan for a randomized controlled trial of surgical fixation with K-wires versus plaster casting in the treatment of dorsally displaced distal radius fractures: DRAFFT2 - Ooms, AG; Png, ME; Cook, JA; Dritsaki, M; Dakin, HA; Costa, ML (British Editorial Society of Bone and Joint Surgery, 2020)
Aims Describe a statistical and economic analysis plan for the Distal Radius Acute Fracture Fixation Trial 2 (DRAFFT2) randomized controlled trial.